Numerical simulation and experimental studies on the ballistic impact characteristics of ceramic/aramid hybrid composite - Ayad, Abed Ramadhan (2012)
Enhancement of the influence of epoxy resin by adding 10% Alumina powder (Al2O3) in the mixture to obtain good mechanical properties of tensile and compression strength has been investigated in this research. The effect of fiber orientation (0o/90o and +45o/-45o) on the composites (kevlar-29/epoxy and kevlar-29/epoxy-Al2O3) and different (45, 50, 55 and 60 %) volume fractions (vf) on the behavior of tensile and compression strength have been studied experimentally in comparison with each other. In addition, the tensile strength testing of Kevlar- 29/epoxy-Al2O3, glass/epoxy-Al2O3 and carbon/epoxy-Al2O3 composites using 50% volume fraction was studied and compared the results obtained of these composites of fiber-epoxy without Al2O3. An application of this research was the study of the fabrication of a novel Hybrid (Ceramic/Aramid) composite based on fiber/metal laminates FML (Kevlar-29/epoxy- Al2O3/Al 6061-T6) that may be comparable to the ARALL-2 (Aramid- Aluminum alloy composite) or GLARE (Glass-Al alloy) composites used in aerospace applications. High velocity impact loading with a range of velocities (160-400 m/s) has been experimentally and numerically investigated. The energy absorption on the ballistic impact characteristics of Hybrid composites has been investigated in this work. The results obtained show that the energy absorption is higher for Kevlar-29/Epoxy backed with 6061-T6 Al alloy with 7.3% at front Al alloy and (5 -6%) reduction in the density and quantity (for 20 mm thickness laminated plates) of Kevlar respectively. he predictions of the energy absorption simulation model using ANSYS AUTODYN 3D v.12.1 are compared with the experimental work. Good agreement is generally obtained with error of 8.7% where it has been shown that these novel sandwich structures exhibit excellent energy absorbing characteristics under high velocity impact loading conditions. Hence the FML presented in this work may be considered as a suitable composite for some aircraft structures.